Early layer formation on K-feldspar during fluidized bed combustion with phosphorus-rich fuel. (1st January 2023) - Faust, Robin; Fürsatz, Katharina; Aonsamang, Panida; Sandberg, Marcus; Kuba, Matthias; Skoglund, Nils; Knutsson, Pavleta
Highlights: The morphology of the bed material influences the tendency for ash retention. Chicken manure ash can be deposited into the cavities of the bed material. Co-combustion of chicken manure and bark causes melt formation. Co-combustion causes formation of an ash layer consisting of Ca, P, Si, K, and S. Interaction of the ashes can improve phosphorus recycling and catalytic activation. Abstract: K-feldspar was utilized as bed material for fluidized bed combustion of bark, chicken manure, and their mixture. Bed samples were extracted after 4 and 8 h and the samples were analyzed with scanning electron microscopy to study the impact of P-rich chicken manure on the bed material. The results were compared to fixed bed exposures with different orthophosphates to investigate their influence in detail. The fresh bed material used for this study exhibited an uneven surface with many cavities which facilitated the deposition and retention of the fuel ash. Utilizing pure chicken manure as fuel led to the formation of Ca- and P-rich particles which accumulated in these cavities. At the same time, larger ash particles were formed which consisted of the elements found in chicken manure ash. The co-combustion of bark and chicken manure led to the interaction of the two ash fractions and the formation of a thicker ash layer, which consisted of elements from both fuel ashes, namely Ca, P, Si, K and S. The layer appeared to be partially molten which could be favorable for the deposition of ash particles and thereby the formation of a mixed Ca/K-phosphate. Fixed bed exposures of the K-feldspar particles with Na3 PO4 or K3 PO4 caused particle agglomeration which means presence of alkali-phosphates should be limited. The co-combustion of bark with chicken manure showed promising results both regarding a shift from Ca-phosphates to more bioavailable Ca/K-phosphates and an acceleration in ash layer formation. The formation of an ash layer after only 4 h of exposure with the mixture of bark and chicken manure could be advantageous for catalytic activation of the bed material.